Local Community-Based Plastic Waste Management in Bangun Village, Mojokerto District - Syabril Ulum, Akhdiyat; Djati, Sasmito; Susilo; Rozuli, Ahmad Imron (Jurnal Pembangunan dan Alam Lestari, 2024)
This research aims to analyze and describe local community-based plastic waste management in Bangun Village, Mojokerto Regency. This research method is a case study because it is based on efforts to understand plastic waste management practices in Bangun Village, identify the role of the community in the plastic waste management process, and evaluate the social, economic, and environmental impacts of local community-based plastic waste management. The research results show the waste management cycle, where at the downstream industrial level, waste producers supply waste to the community, in this case as scavengers. Then, scavengers sell the waste to collectors. Next, collectors sell the waste they buy from scavengers to other consumer industries. The point of the problem occurs at the level of scavengers and collectors, where two cycles occur. However, there is no added value from waste managed by the community. This can be detrimental to the community itself in waste management, both in economic, social, and environmental aspects. For this reason, government intervention is needed to improve the community-based plastic waste management system in Bangun Villages through institutional restructuring to shorten the waste distribution cycle. It is recommended to strengthen support and cooperation from various parties, including the government, society, and the private sector, which is very necessary to create a waste management system that is inclusive, sustainable, and provides benefits for all interested parties. Keywords: management, plastic waste, local community-based, bangun village